Triple-gate Tunnel FETs Encapsulated with an Epitaxial Layer for High Current Drivability - Jang Woo Lee; Woo Young Choi (Journal of semiconductor technology and science, 2017)
The triple-gate tunnel FETs encapsulated with an epitaxial layer (EL TFETs) is proposed to lower the subthreshold swing of the TFETs. Furthermore, the band-to-band tunneling based on the maximum electric-field can occur thanks to the epitaxial layer wrapping the Si fin. The performance and mechanism of the EL TFETs are compared with the previously proposed TFET based on simulation. KCI Citation Count: 3